Knowledge and Self-Protective Practices Against COVID-19 Among Healthcare Workers in Vietnam - Nguyen, Anh Ngoc; Le, Xuan Thi Thanh; Ta, Nhung Thi Kim; Wong, Danny; Nguyen, Nguyen Thao Thi; Le, Huong Thi; Nguyen, Thao Thanh; Pham, Quan Thi; Nguyen, Quynh Thi; Duong, Quan Van; Luong, Anh Mai; Koh, David; et al. (Frontiers in Public Health, 2021)
Background: In middle-income countries such as Vietnam, where healthcare resources are already constrained, protecting healthcare workers (HCWs) is essential for ensuring the sustainability of COVID-19 response in Vietnam. This study was conducted to assess the knowledge and practices regarding the prevention of the COVID-19 among the HCWs in Vietnam to identify the ways of disseminating information to maximize the safety of these essential workers. Methods: An online cross-sectional study, using respondent-driven sampling, was conducted in Vietnam with 742 participants within 2 weeks. The validity of the questionnaire was examined by exploratory factor analysis. Descriptive statistics were used to identify the level of knowledge and practices among the HCWs to prevent the COVID-19. Inferential statistics and regression modeling were used to identify the associated factors with results. Results: Vietnamese HCWs had a high level of knowledge with more than 75% of the participants demonstrating awareness of all the modes of transmission aside from air. The mean knowledge score was 3.7 ± 0.8 (range 1–5). Nearly all the participants relied on the Ministry of Health (98.3%) and the internet (95.5%) for information regarding the COVID-19. The participants endorsed a moderately high level of self-protective practices with mean scores of 4.2 and 3.6 (band score 1–5) for the precautionary and psychological measures, respectively. Nurses were more likely to practice the precautionary measures than doctors and the HCWs at the central level were more likely to practice the psychological measures than those at the district level. Conclusion: Future education initiatives should consolidate the latest literature in an accessible format, focusing initially on the gaps of knowledge regarding aerosol transmission. These initiatives should primarily focus on the doctors, especially those in emergency and intensive care departments.